Business writing in the digital age - Canavor, Natalie , 1942- (SAGE, 2012)
"Business Writing for the Digital Age: A Student's Guide can be used as a core or supplementary text for business writing courses and across the Business and Management curriculum as a student aid to better writing. The text instructs business students how to write for the 21st century business environment in the style it demands: clearly, concisely, powerfully, and with individuality. It also addresses explicitly the digital realm of email, social networking, and social media strategies. The text gives writing teachers a complete structure for teaching business writing that they can adapt to their own preferences. It is also useful for professors who teach general business subjects and recognize a need to help their students write better--a need that is almost universally acknowledged. To serve these dual purposes, the book offers a flexible resource. Its lessons can be taught progressively, drawing on the assignments and discussion questions included. Or, teachers can choose to spend little class time explicitly on writing and instead, assign the book as independent study and evaluate writing progress as a component of regular assigned projects"